PENYEMPURNAAN BENTUK SERTA KETAHANAN MATERIAL PADA DUMMY BODY PART KENDARAAN TEMPUR DENGAN TEKNIK PRINTER 3D DAN KOMPOSIT - Hardy Adiluhung (ATRAT: Jurnal Seni Rupa, 2019)
3D Dimension Printer is a new breakthrough in the world of technology. A 3-dimensional printer is a printer capable of printing three-dimensional objects, not in the form of images or writing on a paper. The advantages of 3-dimensional printers are very possible to make complicated shapes. This is due to the flexibility of printing movements in the three-dimensional scope. Related to the definition, the 3-Dimensional Printer can function important in the world of manufacturing. One manufacturing industry that uses 3-dimensional printer techniques is PT. Pindad Persero, as a solution to accelerate the form of a prototype product development. In the process of the form of a 3-dimensional printer, of course it is always constrained in the results of a less than perfect shape, it is necessary to have a special technique or finishing to perfect the shape. In the form of refinement techniques there are a number of chemical materials such as putty, and composites as a support to accelerate the process up to the basic paint technique. In the technique of improving the shape of the dummy body part of a combat vehicle, of course there needs to be a special technique so that the results are perfect as in the original form. Keywords: 3D Dimensions, Dummy, Composite, Combat Vehicles________________________________________________________________ Printer 3 Dimensi suatu terobosan baru dalam dunia teknologi dengan kemampuan mencetak benda tiga dimensi, bukan berupa gambar atau tulisan di sebuah kertas. Kelebihan dari Printer ini adalah sangat memungkinkan untuk membuat bentuk yang rumit. Hal ini dikarenakan keleluasan gerakan printing pada ruang lingkup tiga dimensi. Terkait dengan defenisinya tersebut maka Printer 3 Dimensi dapat berfungsi penting dalam dunia manufaktur. Salah satu industri manufaktur yang menggunakan teknik printer 3 dimensi adalah PT. Pindad Persero, sebagai solusi untuk mempercepat wujud bentuk dari sebuah pengembangan produk protipe. Dalam proses hasil bentuk printer 3 dimensi, tentu selalu terkendala dalam hasil bentuk yang kurang sempurna, perlu adanya teknik atau finishing khusus untuk menyempurnakan bentuk. Pada teknik penyempurnaan bentuk ada beberapa material bahan kimia seperti dempul, serta komposit sebagai pendukung guna mempercepat proses hingga sampai teknik cat dasar. Dalam teknik penyempurnaan bentuk pada dummy body part kendaraan tempur, tentunya perlu adanya teknik khusus sehingga hasil sempurna seperti pada bentuk aslinya.  Kata Kunci: Printer 3 Dimensi, Dummy, Komposit, Kendaraan Tempur